A replication of "Education and catch-up in the Industrial Revolution" (American Economic Journal: Macroeconomics, 2011) - Jeremy S. S. Edwards (Kiel Institute for the World Economy (IfW), 2017)
Although European economic history provides essentially no support for the view that education of the general population has a positive causal effect on economic growth, a recent paper by Becker, Hornung and Woessmann (Education and catch-up in the Industrial Revolution, 2011) claims that such education had a significant impact on Prussian industrialisation. The author shows that the instrumental variable they use to identify the causal effect of education is correlated with variables that influenced industrialisation but were omitted from their regression models. Once this specification error is corrected, the evidence shows that education of the general population had, if anything, a negative causal impact on industrialisation in Prussia.
http://dx.doi.org/10.7910/DVN/VQTMSZ
Keywords: I25; N13; N63; O14; 330; education; industrialization; Prussia; regional effects; invalid instrument